PELATIHAN ANALISIS KELAYAKAN USAHA KULINER MAKANAN RINGAN DI DESA TATAH PEMANGKIH LAUT KABUPATEN BANJAR - Basuki Basuki; Rahmi Widyanti; Susiladewi Susiladewi (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2021)
The business opportunity of culinary business is very large because currently there arestill promised who do second food while the demand for cookies along with awarenessof people who are increasing in choosing healthy and second food products. The peoplewho work as farmer will to expand its business by increasing their well being in businesssector. Before running the plan, this community conducted a business feasibility study tobe able to decide whether the culinary business plan is feasible or not to be implemented.Based on the results of activity on non-financial aspects of market aspects, marketingaspects, technical aspects and technology, aspects of management and human resourcesand environmental aspects this business feasible to be implemented.